INTER-RELATIONSHIP BETWEEN DRUG USE, ANOMIE, ALIENATION AND AUTTHORITARIANISM AMONGST UNIVERSITY STUDENTS - Agarwal, Ravi K. (Medknow Publications, 1980)
The degree of addictive substance usage score and three personality variables, namely, authoritarianism, alienation, and anomie were measured in 197 university students through a self-administered questionnaire. WHO's Youth Survey Questionnaire for drag use, Varma et al.'s scale of Authoritarianism, Srole's scale of Anomie, and Pearlin's scale of Alienation, were used. A study of the relationship between the co-variables was studied and is discussed.